Government Investment in The Education Sector for Human Capital Development - Muhammad Suhaili; Ani Widayati; Abdul Fatah (The Indonesian Journal of Planning and Development, 2020)
An indicator is considered more representative to be used as a benchmark for development, namely the Human Development Index (HDI). The Human Development Index is another alternative to the definition of development that it is not only economic resources as a means to achieve development goals. The government has made various efforts to improve the quality of education to develop quality human resources. One of the components in the education budget is the education budget through transfers to the regions and village funds. Transfers to regions and village funds consist of general allocation funds and special allocation funds. This study aims to examine the effect of the government’s investment in the education sector through the education budget, particularly Special Allocation Funds-Physical (SAF Physical) and Special Allocation Funds-Non-Physical (SAF Non-Physical) on the Human Development Index (HDI). The study consists of two independent variables, i.e., Special Allocation Funds-Physical (SAF Physical) and Special Allocation Funds-NonPhysical (SAF Non-Physical), and one dependent variable: Human Development Index (HDI). The method used is a quantitative method with multiple regression analysis-ordinary least square (OLS). The data used is secondary data from the Central Bureau of Statistics/Badan Pusat Statistik (BPS) in 2010-2018. The results showed that Special Allocation Funds-Physical (SAF Physical) and Special Allocation Funds-Non-Physical (SAF Non-Physical) significantly influence the Human Development Index (HDI). The Special Allocation Funds-Physical (SAF Physical) has a negative and insignificant effect. In contrast, the Special Allocation Funds-Non-Physical (SAF Non-Physical) has a positive and significant effect on the Human Development Index. Therefore, the government is expected to increase educational investment by allocating more budgets on both physical and non-physical investment to improve the quality of Human Resources.